2005
DOI: 10.1177/1368430205053939
|View full text |Cite
|
Sign up to set email alerts
|

When Do We Communicate Stereotypes? Influence of the Social Context on the Linguistic Expectancy Bias

Abstract: The linguistic expectancy bias (LEB) refers to the tendency to describe expectancy consistent information at a higher level of linguistic abstraction than expectancy inconsistent information. Two experiments examined the influence of the social communicative context on the production of this linguistic bias by manipulating the group membership of the actor in, and the recipient of, stereotypical information. Results supported the prediction that an LEB effect based on stereotypes is especially pronounced in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…As a matter of fact, we found that the tendency to overestimate dispositional causes when making attributions is moderated by the expectations of the perceiver. These results thus show that dispositional attributions are biased in a way that matches the way language abstraction is biased in the language expectancy model (Wigboldus et al, 2000(Wigboldus et al, , 2005. As for the results of Experiment 2, they support our hypotheses based on the language expectancy bias.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As a matter of fact, we found that the tendency to overestimate dispositional causes when making attributions is moderated by the expectations of the perceiver. These results thus show that dispositional attributions are biased in a way that matches the way language abstraction is biased in the language expectancy model (Wigboldus et al, 2000(Wigboldus et al, , 2005. As for the results of Experiment 2, they support our hypotheses based on the language expectancy bias.…”
Section: Discussionsupporting
confidence: 86%
“…In a recent extension of this work, Wigboldus, Semin, and Spears (2000;Wigboldus, Spears, & Semin, 2005) argued that it is not merely the valence of the behavior that prompts different linguistic descriptions but rather observers' expectations. If the behavior corresponds to (contradicts) what observers expect of the target group, then this behavior will be described in more abstract (concrete) terms.…”
Section: Causal Attribution and Language Abstractnessmentioning
confidence: 97%
“…Ingroup to ingroup dyads can achieve closeness, avoid offence (Kurz & Lyons, 2009), and establish common understanding (Clark & Kashima, 2007;Klein, Clark, & Lyons, 2010;Ruscher, 1998) by transmitting stereotype-consistent rather than stereotype-inconsistent material (Lyons & Kashima, 2003Wigboldus, Spears, & Semin, 2005). Even if the initial impressions of an outgroup are moderate and mixed, the net recursive effect of these stereotype communication dynamics can create polarized impressions of the outgroup (Kashima & Woolcock, 2000;Thompson, Judd, & Park, 2000)-in other words, intergroup differentiation.…”
mentioning
confidence: 94%
“…Although blatant intolerance and discrimination are prohibited by law, the expression of prejudice is perpetuated in covert ways. Theories on the role of language in the communication and preservation of social stereotypes are numerous (e.g., Fiedler & Schmid, 2001), and the problem of language as a discriminatory tool has been empirically examined by several investigators (e.g., Maass, Salvi, Arcuri, & Semin, 1989von Hippel, Sekaquaptewa, & Vargas, 1997;Wigboldus, Spears, & Semin, 2005). From an alternative intergroup perspective, it has been proposed that the acquisition and usage of a second language has positive implications in the mitigation of crosscultural conflict and the promotion of intergroup harmony (e.g., Rubenfeld et al, 2007;Wright & Tropp, 2005).…”
Section: Stereotypes and Prejudicial Beliefs Continue To Spread Withimentioning
confidence: 99%